Translation Strategies Used by Donna Widjajanto in Rendering Culture – Specific Items in Diterlizzi’s The Spiderwick Chronicles - Setiawan, Kurnia Ari; Sutopo, Djoko (Universitas Negeri Semarang, 2018)
This study aimed to know the implementation of translation strategies used by the translator and equivalence achievement. Descriptive qualitative research approach is used as research design. The results of the study show that 10 translation strategies used by the translator in rendering 724 culture-specific items data. Translation by repetition or pure borrowing is mostly used the translator as translation strategy containing ecology, concepts of belief and religion, and anthroponyms. The translator intended to source language-oriented in the implementation of translation strategies in translating culture-specific items in The Spiderwick Chronicles because the culture-specific items in TL did not have equal meaning in TL culture. Dealing with equivalence of translation, the translator tends to avoid re-create the culture-specific items in SL. In order to achieve balance, the translator should reduce bringing the original words into target language and avoid the unfamiliar cultural terminologies.